The pilot of geothermal water desalination installation in Poland - TOMASZEWSKA, Barbara; HOŁOJUCH, Grażyna (Geology, Geophysics and Environment, 2011)
The pilot geothermal water desalination installation in Poland was commissioned at the Geothermal Laboratory of the Mineral and Energy Economy Research Institute of the Polish Academy of Sciences (PAS MEERI). Laboratory is localised in Podhale region, in south-eastern Poland. Geothermal waters are extracted from carbonate formations of the Middle Eocene and from Middle Triassic limestones and dolomites. These exhibit relatively low mineralisation - 3 g/dm3. Their temperature at the well outlet ranges 90°C. Installation is supplied with water at a temperature of about 35°C. The capacity has been set at 1 m3/hour of desalinated water. The objective of geothermal water desalination will be to obtain water that meets the requirements stipulated in the regulation of the Minister of Health of 29 March 2007 (Journal of Laws of 2007, No. 61, item 417) concerning the quality of water intended for human consumption. The preliminary results from the geothermal water desalination study conducted at the PAS MEERI are optimistic. In order to validate the assumptions made in the context of industrial applications, further studies have to be conducted in accordance with the project plans. It is certain, however, that the utilization of geothermal water for drinking purposes on an industrial scale will require, first of all, better and more efficient water cooling. Optimum utilization of the thermal waters obtained is an important issue for most geothermal plant both in Poland and abroad. Efficient geothermal water management has one main goal: optimizing system operation and improving the economics of geothermal plant operation. Additionally, the use of cooled water for drinking purposes, particularly for open drain installations (without injecting cooled water into the formation) will contribute to the comprehensive utilization of geothermal water and the decentralization of drinking water production. Therefore the present study concerns two significant research areas: geothermics (cooled water utilization methods) and hydrogeology (water management).